Strategic Approaches to Social Freedom in Nigeria: Exploring Freire’s Pedagogy of the Oppressed (American International Journal of Supply Chain Management, 2020)
The study interrogated Freire’s Pedagogy of the Oppressed as a solution to social injustice in Nigeria. The purpose of adopting the work of this great Philosopher is to examine critically and analyse how the Brazilians were able to solve social injustices in their country. The study employed analytic and prescriptive techniques in philosophy to handle issues that aroused in the cause of this study so as to avoid ambiguity. The paper revealed that individual’s role in achieving social freedom and community development through critical discussion, critical reflection, and unity/love critical action is very important. The study concluded that education that develops social consciousness in individuals should be encouraged in order to solve the problem of class distinction, inequality and social injustice in regards to holistic development of Nigeria as a community. It recommended that there should be means of mass sensitisation which includes all educational outlets, media houses, Non-Governmental Oganisations (NGOs) and Philanthropists Sponsored Programmes (PSPs). Trade Unions (TUs), professional bodies, political parties, religious organisations and traditional institutions are to sensitise their members on the need for active participation and contribution to governance.